Efektivitas Sistem Administrasi Pemerintahan Daerah terhadap Kinerja Pengelolaan Anggaran Pendapatan dan Belanja Daerah (APBD) - Luthfi Azhari; Tumija, Tumija; Restu Widyo Sasongko (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to evaluate the effectiveness of the local government administrative system in improving the management performance of the Regional Revenue and Expenditure Budget (APBD). The method used is a literature review by analyzing various previous studies, official reports, and policy documents related to APBD management at the regional level. The results show that a well-structured administrative system can accelerate the planning, implementation, and reporting processes of the APBD, although challenges remain in inter-unit coordination and the utilization of information technology. To enhance effectiveness, it is recommended to strengthen human resource capacity, update financial information systems, and reinforce internal oversight. These findings contribute to efforts to achieve more accountable, efficient, and transparent regional financial governance.